Perancangan Sistem Monitoring Pembangkit Listrik Termoelektrik Generator Pada Aplikasi Petrikor Berbasis Internet of Things - Apolanni, Rafi Anwar (Peneliti.net, 2025)
Generator Thermoelectric Power Plant (PETRIKOR) is an innovative technology capable of generating electricity from a temperature difference. However, to improve efficiency and optimize PETRIKOR performance, remote monitoring and management is a critical factor. This system also allows manual control to optimize electricity production from PETRIKOR according to changes in the environment or power demand. Furthermore, the Kodular platform for IoT applications is used to connect the PETRIKOR system to the internet, so that data can be accessed and monitored remotely via a mobile or smartphone application. The result of this research is a monitoring and control system for PETRIKOR that is efficient and easily monitors the operational conditions of PETRIKOR. It is hoped that this research can make a positive contribution to the application of PETRIKOR technology in real environments and facilitate the integration of IoT-based sustainable energy systems.Keywords: Thermoelectric Power Plant Generator, Power Optimization, Heat Utilization, Seebeck Effect, Peltier.